A longitudinal application of three health behaviour models in the context of skin protection behaviour in individuals with occupational skin disease - Matterne, Uwe; Diepgen, Thomas L.; Weisshaar, Elke (Psychology & health, 2011)
Occupational skin disease (OSD) is common, associated with poor prognosis and poses a significant burden to the individual and society. We applied the theory of planned behaviour (TPB), the prototype-willingness model (PWM) and the health action process approach (HAPA) to the prediction and explanation of occupationally relevant skin protection behaviour in individuals with OSD. We used a longitudinal design. In this study, 150 individuals participating in a 3-week inpatient tertiary prevention programme completed measures assessing the constructs of the TPB, PWM and HAPA at admission (T 0), discharge (T 1) and once the individual had returned to work and worked for 4 consecutive weeks (T 2) (n = 117). Intention was measured at T 0 and skin protection behaviour at T 2. Path analysis was used to assess the longitudinal associations of the models’ constructs with intention and skin protection behaviour. TPB as well as PWM variables accounted for 30% of variance in behaviour, HAPA variables for 33%. While not all predictions were confirmed by the data, all three models are able to inform us about the formation of skin protection intention and behaviour in individuals with OSD. The findings are discussed in light of future interventions and research.
Gesehen am 12.08.2022